Time, money, and support: Student-Athletes` transition to high achievement sport - Bengtsson, S.; Johnson, U. (Athletic Insight - The Online Journal of Sport Psychology, 2012)
The aim of this study was to examine the perceptions of within-career transition, as experienced by student-athletes striving to reach the international level. Interviews were used to examine the perceptions of 26 Swedish student-athletes with a mean age of 22.5 years practicing individual sports at the national elite level, involved in a career assistance program. Categories identified through thematic content analysis were changes experienced in the transition, the career assistance program, resources to adjust to the new level in sport, satisfaction with their current situation, and strategies to adjust to the new level in sport. The athletes highlighted the value of interpersonal support and commitment, and recognized the need to develop further coping strategies, such as stress and time management. Practical implications for promoting successful within-career transitions are discussed.